ZnO nanorod arrays grown on an AlN buffer layer and their enhanced ultraviolet emission. Issue 41 (4th October 2017) - Ali, Amany; Wang, DongBo; Wang, JinZhong; Jiao, ShuJie; Guo, FengYun; Zhang, Yong; Gao, ShiYong; Ni, ShiMing; Luan, ChunYang; Wang, DaiZhe; Zhao, LianCheng
Abstract : The ultraviolet luminescence of ZnO nanorods was greatly enhanced through introducing an AlN buffer layer. Abstract : n-ZnO nanorods/p-Si heterojunctions with and without an AlN buffer layer were grown. The ultraviolet luminescence of the ZnO nanorods was greatly enhanced through introducing an AlN buffer layer, and this can be attributed to an improvement in the ZnO nanorod crystallinity, and confinement effects from the AlN potential barrier layer.